An Insight into the Synthetic Strategies and Pharmacological Effects of Cinnoline Derivatives - Saxena, Shagun; Mishra, Rakhi; Mazumder, Avijit; Mazumder, Rupa; Shuaib, Mohd (Indian Journal of Pharmaceutical Education and Research, 2025)
Background The cinnoline ring is a new aromatic heterocyclic connected with two nitrogen atoms in a 6 membered ring and compounds containing this ring have been shown to have a wide variety of pharmacologicaleffects. Objectives This review studyextensively explains the synthetic strategy by which researchers have produced cinnoline derivatives reported to have numerous pharmacological effects, including antitubercular, antibacterial, anticancer, antimolluscidal, etc., Materials and Methods The cinnoline moiety is a highly powerful lead that may give a range of pharmacological effects and this study provides brief information on the various synthesis techniques and pharmacological activity of reported cinnoline analogs that support this claim. Results This succinct review summarizes the several known cinnoline analogs, outlining their respective synthesis strategies and pharmacological activity and conclusively showing that the cinnoline moiety is a potent lead capable of producing a wide range of therapeutic actions. Conclusion This article’s literature review will serve as a springboard for further research into the synthesis of cinnoline derivatives, which in turn will aid in the creation of cinnoline-based compounds with improved pharmacokinetic and pharmacodynamic characteristics.
Keywords: Cinnoline; Aromatic; Synthesis; Pharmacokinetic; Heterocyclic; Pharmacological effects